Efficient Shadow Removal Using Subregion Matching Illumination Transfer. (25th November 2013) - Xiao, Chunxia; Xiao, Donglin; Zhang, Ling; Chen, Lin
Abstract: This paper proposes a new shadow removal approach for input single natural image by using subregion matching illumination transfer We first propose an effective and automatic shadow detection algorithm incorporating global successive thresholding scheme and local boundary refinement. Then we present a novel shadow removal algorithm by performing illumination transfer on the matched subregion pairs between the shadow regions and non‐shadow regions, and this method can process complex images with different kinds of shadowed texture regions and illumination conditions. In addition, we develop an efficient shadow boundary processing method by using alpha matte interpolation, which produces seamless transition between the shadow and non‐shadow regions. Experimental results demonstrate the capabilities of our algorithm in both the shadow removal quality and performance.